Relationship between various pathways of cellular death at distinct stages of ontogenesis in normal state and systemic diseases of connective tissue - V. I. Shishkin (SPb RAACI, 2020)
The aim of our research  was to reveal quantitative ratios existing between  the pathways of cellular death in normal state, as well as in immunocomplex pathology. The proportion of different pathways of cell death (autophagy, apoptosis, necrosis) in autoimmune (systemic  connective tissue diseases (SDCT) – rheumatoid arthritis (RA), systemic lupus erythematosus (SLE)  and systemic scleroderma (SSD) is a subject of age-related changes. On the one hand, aging process can be considered a genetically determined overall decrease in adaptive potential of the body, and a systemic  age-related chronic inflammatory response, with a pronounced cytokine proinflammatory shift. On the other hand, a polygenic decrease in energy and information capacity  of the cells, represent the basis of multisystem and multiorgan functional and metabolic disorders  in SDCT.Blood plasma  samples were analyzed  in the patients of two age groups. The first group consisted of 10 SLE cases (4 men and 6 women, average age 43.8 years), 13 patients with RA (5 men and 8 women, average age 45.6 years),  7 SSD (women, average age 35.8 years),  and 10 healthy  donors  (6 men and 4 women, average age 40.7 years). The second age group consisted of 9 SLE cases (2 men and 7 women, average age 69.8 years), 10 patients with RA (5 men and 5 women, average age 65.6 years), 5 patients with SSD (women, average age 65.7 years) and 12 healthy  donors  (normal biological  aging – 7 men and 5 women, average age 64.7 years). The data presented in this paper  were obtained with informed consent of the  patients. When  carrying  out  biomedical research, we followed  internationally recognized ethical  standards of the Helsinki Declaration (International Medical Association, 1996, revision  2013). The proportion of various cell death  types (autophagy, apoptosis, necrosis) in  autoimmune disorders  (systemic  diseases  of connective tissue,  SDCT), i.e.,  rheumatoid arthritis (RA), systemic  lupus erythematosus (SLE), and systemic  scleroderma (SSD) proved to be subject to age-dependent changes. Close  interaction were revealed  between  the  ways of cellular  death  in SDCT (most  pronounced in SLE), correlating with age changes and clinical  manifestations of autoimmune process. In SDCT, the affected tissues exhibit all types of cellular  death, however, degree of their expression  depends on the disease nosology. Upon systemic diffuse pathology of connective tissue, autophagy (especially in case of SLE and RA) is directly involved in development of immune response  and inflammatory process.In normal biological  aging, like as in SDCT, one may observe a sharply increased activity of the metabolic trigger – AMP-activated protein kinase (AMPK), a sensor of intracellular energy, along with shifted acid-base equilibrium. The quantity of active oxygen radicals  increases, oxidoreductive potential of the cells is changed, with  activation of cellular  destruction components. Activity  of cytokine system  in the  organism  is changed causing  apoptosis regulation; expression  of chaperons is decreased, and  the immune-oxygenase homeostasis is also displaced. Inhibition of genetically determined process of death  of cells (apoptosis) comprises the basis for development of autoimmune diseases. Transition of late apoptosis into secondary necrosis  is accompanied by decrease of antioxidant protection and  development of autoimmune pathology. The  chaperon-mediated induction of immune response as the signaling mechanism of autophagy, being evolutionarily fixed in mammals only, may be the common central  link and “the  molecular switch”  causing both development of autoimmune diseases of connective tissue, and aging processes.